2022
DOI: 10.3390/jcm11020297
|View full text |Cite
|
Sign up to set email alerts
|

A Large Gap in Patients’ Characteristics and Outcomes between the Real-World and Clinical Trial Settings in Community-Acquired Pneumonia and Healthcare-Associated Pneumonia

Abstract: (1) Introduction: Evidence-based medicine (EBM) is necessary to standardize treatments for infections because EBM has been established based on the results of clinical trials. Since entry criteria for clinical trials are very strict, it may cause skepticism or questions on whether the results of clinical trials reflect the real world of medical practice. (2) Methods: To examine how many patients could join any randomized clinical trials for the treatment of community-acquired pneumonia (CAP) and healthcare-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(31 reference statements)
1
1
0
Order By: Relevance
“…Moreover, patients in the RCT inappropriate group showed significantly lower OSs than those in the RCT appropriate group. This remarkable trend was reproducible in previous studies [ 2 , 18 ]. In terms of mortality among IE patients, the mortality rate in RCT was much lower than our cohort, showing 2.9–18% of in-hospital mortality rate [ 17 , 19 , 20 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, patients in the RCT inappropriate group showed significantly lower OSs than those in the RCT appropriate group. This remarkable trend was reproducible in previous studies [ 2 , 18 ]. In terms of mortality among IE patients, the mortality rate in RCT was much lower than our cohort, showing 2.9–18% of in-hospital mortality rate [ 17 , 19 , 20 ].…”
Section: Discussionsupporting
confidence: 91%
“…Since EBM is considered to be the highest level of medical practice, physicians tend to prioritize it in general practice, and some are overconfident in RCTs. As the data showed, EBM based on RCT is very limited in scope, and EBM has never reflected the real world as previous studies have already reported [ 2 , 18 ].” IE patients in the real world are quite different from those who can be enrolled in a clinical trial, showing an unfavorable outcome. Only 26% (17 of the 66) of patients were appropriate for RCT enrollment.…”
Section: Discussionmentioning
confidence: 98%